Optimal Couples of Rearrangement Invariant Spaces for Generalized Maximal Operators. (19th March 2014) - Ahmed, Irshaad; Nazeer, Waqas
Abstract : The optimal couples of rearrangement invariant spaces for boundedness of a generalized maximal operator, associated with a quasiconcave function, have been characterized in terms of certain indices connected with rearrangement invariant spaces and quasiconcave functions.